$(3,2)$-fuzzy UP-subalgebras and $(3,2)$-fuzzy UP-filters - Young Bae Jun; B. Brundha; N. Rajesh; Ravikumar Bandaru (Journal of Mahani Mathematical Research)
The aim of this article is to apply a $(3,2)$-fuzzy set to the UP-subalgebras and UP-filters of UP-algebras. The concepts of $(3,2)$-fuzzy UP-subalgebra, $(3,2)$ -fuzzy near UP-filter and $(3,2)$ -fuzzy UP-filter in UP-algebras are introduced and  several properties, including their relations, are investigated. The conditions under which the $(3,2)$-fuzzy UP-subalgebra $($resp., $(3,2)$ -fuzzy near UP-filter$)$ can be the $(3,2)$-fuzzy near UP-filter $($resp., $(3,2)$-fuzzy UP-filter$)$ are searched. The characterizations of $(3,2)$-fuzzy UP-filter is provided and the relationship between intuitionistic fuzzy UP-subalgebra and $(3,2)$-fuzzy UP-subalgebra is discussed. We use fuzzy UP-subalgebra $($resp., fuzzy near UP-filter, fuzzy UP-filter$)$ to create a $(3,2)$-fuzzy UP-subalgebra $($resp., $(3,2)$-fuzzy near UP-filter, $(3,2)$-fuzzy UP-filter$)$.